Pengaruh Video Tutorial Terhadap Hasil Belajar Menggambar Model pada Siswa Kelas X SMKN 1 Siborongborong - Sihar Manaek Gultom; Sugito Sugito (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to examine the effect of using video tutorial media on learning outcomes to draw models at SMK Negeri 1 Siborongborong and improve students' ability to draw models compared to learning that is being applied by cultural arts teachers, namely using image media that is imitated by students. The problem is focused on how much significant influence the use of video tutorial media has on learning outcomes to draw models. This research uses experimental quantitative research by determining the sample cluster random sampling in class X students at SMK Negeri 1 Siborongborong. This research data was given two stages of action, namely initial sampling with the teaching and learning process without using video tutorials and data collection methods used include documentation, observation and test methods.